Acute stress and fear scales during the COVID-19 pandemic: development and evaluation in a Costa Rican sample - Jurado-Solórzano, Ana María (2024)
Objective: In the context of the pandemic due to SARS-CoV-2, concerns were raised about how to adequately assess its impact on the wellbeing of the population. The main reason of this paper is to present the preliminary results of psychometric properties of measures created to evaluate such impact. Method: We created and adapted several assessment instruments, and validated them with a volunteer sample of 699 adults (+18), inhabitants of Costa Rica, who filled out an online questionnaire on mental health consequences of the pandemic during September 2020. Results: The results provided evidence of validity and reliability for the new scales developed. Also, they show a negative correlation between resilient coping and acute stress, which could be considered evidence of discriminant validity. Conclusion: In this order, the measures showed acceptable  psychometric properties with the evaluated sample. Future research is needed to gather more evidence of reliability and validity in probabilistic samples.